Identifikasi Hasil Pengembangan Soal Tryout Mahasiswa Pendidikan Profesi Guru - Sumari, Sumari; Faizah, Siti (JoEMS (Journal of Education and Management Studies), 2025)
This study aims to analyze the quality of the tryout instrument for students of the Industrial Chemical Engineering Professional Education (PPG) Study Program through the validity and reliability test of the questions. The method used is descriptive quantitative with 29 students as research subjects. The instrument consists of 35 multiple-choice questions analyzed using Corrected Item-Total Correlation for validity and Cronbach's Alpha for reliability. The results showed that of the 35 questions, only about 20-25% met the validity requirements, while the rest were declared invalid. The reliability value of the first instrument was 0.565 which is included in the low-sufficient category. After item selection and leaving 11 questions, the reliability increased significantly to 0.804 which is included in the good category. This finding indicates that the quality of the instrument is determined more by the quality of the questions, not the number of questions. The second instrument is more valid and reliable so it can be used for learning evaluation, while the first instrument requires revision. In this case, the second instrument is the result of a selection of the first instrument, not two different instruments. Therefore, it is necessary to revise the tryout questions so that the questions developed are not too easy for PPG students in the Industrial Chemical Engineering Study Program.